A study on pattern of dermatoses affecting periorbital region and its clinicodermoscopic correlation - Namrata Bhavsar; Pragya Ashok Nair (Wolters Kluwer Medknow Publications, 2021)
Background: The periorbital area may be affected by a vast number of dermatoses such as infectious or noninfectious diseases, inflammatory dermatoses, systemic diseases, drug reactions, benign and malignant lesions, and traumatic lesions, thus poses both diagnostic and therapeutic challenge. Objectives: To study the pattern of dermatoses involving periorbital region and to correlate its clinical and dermoscopic findings. Materials and Methods: A cross-sectional study was carried out in patients with periorbital dermatoses (PODs) attending the Department of Dermatology during April 2018-March 2019 after approval from the ethical committee. A detailed history was taken and investigations including hemoglobin levels, Vitamin B12, serum cholesterol, and wood's lamp examination were done as and when required. A prestructured pro forma was used to collect the data. Data were entered into Microsoft Excel 2010 and analyzed using EPI INFO. Ver7 software (Developed by united states of America centre for disease control. Results: A total of 275 patients were studied of which majority of patients belonged to the age group of 41-60 years (38.5%) with a female-to-male ratio of 1.16:1. The most common group of PODs was skin tumors (25.1%), followed by disorders of pigmentation (17.4%), infections (13.1%), and periorbital dermatitis (11.6%). Most common dermoscopy findings of PODs were as follows: (a) common seborrhoeic keratosis (CSK): comedone-like opening, fissures and ridges, and sharp demarcation; (b) verruca vulgaris: finger-like papilla, red brown dots in center of papilla; (c) periorbital hyperpigmentation: blotches, globules, exaggerated pigment network, and reticular vessels; (d) allergic dermatitis: patchy red dots, pinkish hue, and patchy scale; (e) senile comedone: comedone-like opening; and (f) xeroderma pigmentosus: orange-yellow homogenous structures. Conclusion: Periorbital region is an area of cosmetic concern. Dermoscopy improves the differential diagnosis of common PODs and its knowledge may aid to reduce unnecessary invasive procedures such as shaving or incisional biopsies which may lead to scarring.